O mais esquisito dos espetáculos : a crise do asilo diplomático entre Brasil e Portugal em 1894 - Santos Júnior, João Júlio Gomes dos (2014)
The Revolta da Armada (Brazilian Naval Revolt of 1893) ended on March 13, 1894 with the granting of asylum to 518 Brazilian belligerents aboard two Portuguese warships. This dissertation seeks to understand how Brazil and Portugal s differing interpretations of the political status of the asylum-seekers resulted a diplomatic crisis between the two countries. This dispute did not remain a bilateral affair: both governments pursued international diplomatic support for their respective points of view. The ships that carried the sailors, the Mindello and the Affonso d Albuquerque, were small and poorly equipped, precluding the possibility of making the long trip to Lisbon. Because the corvettes set sail for the Rio de la Plata from Rio de Janeiro, the governments of Argentina and Uruguay also actively participated in the diplomatic discussion of the sailors status. Diplomats, ministers, institutional representatives, commandants, and the sailors themselves expressed their differing understandings of their status in a lively corpus of correspondence, consciously deploying certain concepts to reinforce their political discourses. Analysis of these communications points to the existence of a broad dispute over the political status of the combatants and an adjustment of strategies depending on place and interlocutors understandings of political asylum. The asylum-seekers escape to Buenos Aires and later Montevideo caused Brazil to cut diplomatic relations with Portugal.